2013
DOI: 10.1111/tmi.12229
|View full text |Cite
|
Sign up to set email alerts
|

Water quality risks of ‘improved’ water sources: evidence from Cambodia

Abstract: Abstractobjectives The objective of this study was to investigate the quality of on-plot piped water and rainwater at the point of consumption in an area with rapidly expanding coverage of 'improved' water sources.methods Cross-sectional study of 914 peri-urban households in Kandal Province, Cambodia, between July-August 2011. We collected data from all households on water management, drinking water quality and factors potentially related to post-collection water contamination. Drinking water samples were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 48 publications
3
75
2
Order By: Relevance
“…These results are consistent with the findings of other studies that demonstrated improved sources are not necessarily safe. 5,6,8,[25][26][27][28] Although transporting water to the home from an offpremises source has been associated with contamination in other studies, 15,17 in this population, microbiologic quality of stored water tended to be similar to, or better than, source water. Under conditions of relatively high-quality source water as in this study, microbial settling and time-related die-off are unlikely to yield significant improvement in water quality.…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with the findings of other studies that demonstrated improved sources are not necessarily safe. 5,6,8,[25][26][27][28] Although transporting water to the home from an offpremises source has been associated with contamination in other studies, 15,17 in this population, microbiologic quality of stored water tended to be similar to, or better than, source water. Under conditions of relatively high-quality source water as in this study, microbial settling and time-related die-off are unlikely to yield significant improvement in water quality.…”
Section: Discussionmentioning
confidence: 97%
“…However, leaking pipes and intermittent service can compromise the quality of piped water (Kumpel and Nelson, 2014), and fecal contamination of piped water is frequent in low-and middle-income countries, particularly in rural areas (Bain et al, 2014a;Christenson et al, 2014). Additionally, several included studies reported that water obtained on plot was stored in containers and subsequently contaminated; this was reported in a recent study in Cambodia, which also found that water collected on-plot was frequently stored in the same container with water from unimproved sources (Shaheed et al, 2014). Measured water quality was not associated with diarrhea except in households with on-plot water supply, water storage, and toilets (van der Hoek et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In our study of the quality of household water from "improved" sources in Cambodia, we observed substantial and statistically significant contamination of drinking water during storage. 19 Arithmetic mean counts of E. coli in stored household tap water were significantly higher than those in samples taken directly from the tap. 19 Despite a wealth of evidence indicating that safe storage of water lowers the risk of exposure to waterborne microbes associated with diarrhoea, there have been few epidemiological studies of safe water storage with health measures as outcomes.…”
Section: Water Safety Compromised By Storagementioning
confidence: 99%
“…19 Arithmetic mean counts of E. coli in stored household tap water were significantly higher than those in samples taken directly from the tap. 19 Despite a wealth of evidence indicating that safe storage of water lowers the risk of exposure to waterborne microbes associated with diarrhoea, there have been few epidemiological studies of safe water storage with health measures as outcomes. While several trials of household water treatment have included interventions that included safe storage, 20,21 only two published unblinded studies have attempted to measure a reduction in diarrhoea as the result of safe storage alone.…”
Section: Water Safety Compromised By Storagementioning
confidence: 99%
See 1 more Smart Citation